International business : the challenges of globalization - Wild, John J. (Pearson, cop., 2012)
For introductory International Business courses with the need for a brief, accessible text. This title is a Pearson Global Edition. The Editorial team at Pearson has worked closely with educators around the world to include content which is especially relevant to students outside the United States. A comprehensive yet concise framework with unrivaled clarity. International Business: The Challenges of Globalization presents international business in a comprehensive yet concise framework with unrivaled clarity. Recent, real-world examples and engaging features brings the material to life for students.